The modernization of the agricultural sector and rural-urban migration in Colombia (1973)
This article is an extended and up-dated version of a paper -ith the same title published as Occasional Paper No. 1 of the Institute of Latin-ALerican Studies, University of Glasgow, 1971. It is being published in Spanish in La_nevista Colombianade Economfa ARrIcola, Vol. 4, 1971. The author is indebted to Professor Lauchlin Currie for his considerable help and encouragement3n the preparation of this paper. The views expressed herein remain the author's sole responsib-ility. 1. J.C.F.Fei and G.Ranis, Development of the LabDurlSurplus Economy, Hoi,evood, Illinois, 1964; D. Jorgenson, "The Development of a Dual Economy", Economic Journal, June 1961, pp. 309-334; B.F.Johnston and J.:ellor, "The Role of Agriculture in Economic Development", American Economic Review, 1961, pp. 566-593. 2. 7.H.Nicholls, "The Place of Agriculture in Economic Development", in C.Eicher and L."itt (eds.), Agriculture in ,-;conouic Development, New York, 1964, pp. 11-44. 3. The underlining is by the present autor.